Analisis Penerapan Pembelajaran Organisasi pada PT. PLN Cabang Padang - Fermayani, Riche (Jurnal Ekonomi, 2013)
This research is aimed to know the implementation of the oraganizational learning process PT. PLN (Persero) by a research. Research design is desciptive study used to describe the current conditions (current status) of a population. PT. PLN Cab. Padang has a number of employees as many as 156 peopleof the 122 poeple were selected as sample. Analysis of research data to describe the conclution of each variable using the central tendency base on the value of the average (mean) of the respondents answers. Overall, the result shows that discipline has existed well, mental models descipline average respondents who obtained the well existed; descipline share vision, the average value for each element of the resulting indicate that shared vision has had a good existence; learning discipline team show that the average value of the studied elements produce a good aplication value in the existence of the internal environment PLN; and on the whole it can be said that organizational learning has been implemented well in the internal environment PLN.